Problems in translating modern computer terms from english into kazakh language - Шaдкaм З.; Сұлтaнбaевa Н. Д. (Journal of Oriental Studies, 2017)
This article focuses on the problems of computer terms’ translation, importance and basic methods of translation. In our country, there is a special commission of translation of terms and because of its importance they pay much attention to it. Therefore, at the present time special terminological dictionaries are published periodically. In addition, the article provides information on foreign and domestic experts of Translation Studies on issues of translation and translation of computer terms.